2017
DOI: 10.3329/bsmmuj.v10i2.31910
|View full text |Cite
|
Sign up to set email alerts
|

Effect of raised serum uric acid level on perinatal and maternal outcome in cases of pregnancy-induced hypertension

Abstract: <p>The aim of this study was to find out the effects of raised serum uric acid level on perinatal and maternal outcome in cases of pregnancy-induced hypertension. One hundred pregnant women with gestational period beyond 28 weeks with pregnancy-induced hypertension-preeclampsia and eclampsia were included in this study and divided into two groups. Group A (n=65) patients with a serum uric acid level &gt;6 mg/dL was compared to Group B (n=35) patients with a uric acid level &lt;6 gm/dL. It reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
1
3
0
Order By: Relevance
“…Regarding the socio-demographic features observed in the present study, it was found that the mean age of presentation in Gestational hypertension, Pre-eclampsia, and Eclampsia groups were 26.51 ± 3.82 years, 27.14 ± 3.64 years and 24.73 ± 4.01 years respectively, with maximum cases of pre-eclampsia and eclampsia occurring in women of 20-25 years of age group. This is similar to the results of various other studies which have reported that the highest incidence of HDP was found in women of age group 21-25 years [24, 25]. In our study, we have also observed that the women with severe pre-eclampsia belonged to 22-35 years of age group and in eclampsia 19-32 years.…”
Section: Discussionsupporting
confidence: 92%
“…Regarding the socio-demographic features observed in the present study, it was found that the mean age of presentation in Gestational hypertension, Pre-eclampsia, and Eclampsia groups were 26.51 ± 3.82 years, 27.14 ± 3.64 years and 24.73 ± 4.01 years respectively, with maximum cases of pre-eclampsia and eclampsia occurring in women of 20-25 years of age group. This is similar to the results of various other studies which have reported that the highest incidence of HDP was found in women of age group 21-25 years [24, 25]. In our study, we have also observed that the women with severe pre-eclampsia belonged to 22-35 years of age group and in eclampsia 19-32 years.…”
Section: Discussionsupporting
confidence: 92%
“…In a cross-sectional study conducted in Nepal amongst 90 pregnant women between 24 to 36 weeks of gestation, mean serum uric acid levels were higher in the pregnancyinduced hypertension group compared to the control group; 5.46mg/dL (324.8µmol/L) versus 4.03mg/dL (239.7µmol/L) 17 . Ahmad et al 18 reported that amongst 100 pregnant women who developed pre-eclampsia and serum uric acid was taken at mean gestational age of 33.5 weeks, had mean uric acid levels of 7.01mg/dL (417µmol/L). A meta-analysis on the prognostic role of serum uric acid in pre-eclampsia 19 included 196 studies involving 39540 women, found that higher uric acid was estimated for severe pre-eclampsia, eclampsia, haemolysis, elevated liver enzymes, and low platelet syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Serum uric acid level was negatively correlated to maternal serum AAT, in line with the earlier studies linking serum uric acid with intrauterine growth restriction, low Apgar score, and even fetal death. 14,15 One of the fetal adaptive mechanisms to hypoxia is increased kidney resistance, which decreases urine output and AFI, explaining the negative correlation with AAT. 14 Platelet indices showed a strong inverse correlation with AAT serum level in accordance with Nori et al, 16 who described that the consumed platelets will stimulate the bone marrow to produce new broader and larger platelets.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress initiates injury into endothelial cells and triggers a cascade of an inflammatory response (including AAT) that alters platelet indices and numbers. 15 Further, blood vessels and arterioles will suffer spasms, increasing the mean blood pressure and reduced blood supply to the vital organ. Reduced fetal nutrient decreases fetal weight and fetal weight percentile.…”
Section: Discussionmentioning
confidence: 99%